2018
DOI: 10.18502/kss.v3i10.2925
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Female Genital Circumcision in Indonesian Transition Society: Revealing a Hope

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…According to United Nation Commission for Human Rights, FGC is recognized as a violation of women's right in health, security, and physical integrity. It confirms as a violence against women which threat to reproductive health 15 . UN also move a campaign of zero tolerance toward FGC practices, as there are more than 150 million of women had suffer from the genital cutting 16 .…”
mentioning
confidence: 90%
“…According to United Nation Commission for Human Rights, FGC is recognized as a violation of women's right in health, security, and physical integrity. It confirms as a violence against women which threat to reproductive health 15 . UN also move a campaign of zero tolerance toward FGC practices, as there are more than 150 million of women had suffer from the genital cutting 16 .…”
mentioning
confidence: 90%
“…According to United Nation Commission for Human Rights, FGC is recognized as a violation of women's right in health, security, and physical integrity. It confirms as a violence against women which threat to reproductive health (Imelda, Djamilah, Kartikawati, Mahendro, & Ratri, 2018). UN also move a campaign of zero tolerance toward FGC practices, as there are more than 150 million of women had suffer from the genital cutting (Natsir, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Almost half of the girls under the age of 12 have undergone some form of FGM/C in Indonesia, mostly between the ages of 1-5 months (4). In a recent study, Type 4, Type 1 and symbolic methods were most commonly found in seven regions (7). Closely linked to Islamic teachings (8), with the advent of Western medicine, the discourse for FGM/C shifted to hygiene (9).…”
mentioning
confidence: 99%